Integration of chemical looping oxygen production and chemical looping combustion in integrated gasification combined cycles. (15th May 2018) - Cloete, Schalk; Giuffrida, Antonio; Romano, Matteo; Chiesa, Paolo; Pishahang, Mehdi; Larring, Yngve
Highlights: COMPOSITE is a new concept for highly efficient power production with CO2 capture. Chemical looping oxygen production (CLOP) is used for air separation. CLOP reactors are synergistically integrated into a PBCLC-IGCC power plant. COMPOSITE achieves up to 45.4% efficiency with 95% CO2 capture from coal. Efficiency is 8.1%-points better than IGCC with pre-combustion capture. Abstract: Energy penalty is the primary economic challenge facing CO2 capture technology. This work aims to address this challenge through a novel power plant configuration, capable of achieving 45.4% electric efficiency from coal with a 95% CO2 capture efficiency. The COMPOSITE concept integrates chemical looping oxygen production (CLOP) and packed bed chemical looping combustion (PBCLC) reactors into an integrated gasification combined cycle (IGCC) power plant. Hot gas clean-up technology is implemented to boost plant efficiency. When commercially available cold gas clean-up technology is used, the plant efficiency reduces by 2%-points, but remains 2.3%-points higher than a comparative PBCLC-IGCC power plant and 8.1%-points higher than an IGCC power plant with pre-combustion CO2 capture. It was also shown that the COMPOSITE power plant performance was not sensitive to changes in the performance of the CLOP reactors, implying that uncertainties related to this novel process component do not reduce the potential of the COMPOSITE concept. The outstanding efficiency obtained for this concept is made possible by a complex and highly integrated plant configuration, whose operability and techno-economic feasibility must be demonstrated.